Pengaruh imej badan dan penghargaan kendiri ke atas kebimbangan sosial dalam kalangan mahasiswa di Malaysia - Siti Anisah Muhamad Johan,; Roseliza Murni Ab. Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aimed at investigating the role of body image and self-esteem in predicting social anxiety amongst students from two universities in Malaysia. A total of 320 students were recruited in this study, of which 168 were the students of Universiti Kebangsaan Malaysia and another 152 were the students of Universiti Kuala Lumpur. Three scales were adopted in this study whereby the Rosenberg Self-Esteem (RSE) scale was used to measure self-esteem, the Multidimensional Body-Self Relation Questionnaire (MBSRQ) was used to measure body image, while Social Phobia Inventory (SPIN) was used to measure social anxiety. Multiple regression analysis was conducted to measure the predictive value of body image and selfesteem on social anxiety. The findings revealed that self-esteem and four dimensions of body image namely fitness orientation, appearance evaluation, health evaluation and health orientation significantly predicted social anxiety amongst the study sample. Hence, implying the importance of self-esteem and some dimensions of body image in influencing social anxiety.